Effects of coherence on quantum speed limits and shortcuts to adiabaticity in many-particle systems - Tian-Niu Xu; Jing Li; Thomas Busch; Xi Chen; Thomás Fogarty (Physical Review Research, 2020)
We discuss the effects of many-body coherence on the speed of evolution of ultracold atomic gases and the relation to quantum speed limits. Our approach is focused on two related systems, spinless fermions and the bosonic Tonks-Girardeau gas, which possess equivalent density dynamics but very different coherence properties. To illustrate the effect of the coherence on the dynamics, we consider squeezing an anharmonic potential which confines the particles and find that the speed of the evolution exhibits subtle but fundamental differences between the two systems. Furthermore, we explore the difference in the driven dynamics by implementing a shortcut to adiabaticity designed to reduce spurious excitations. We show that collisions between the strongly interacting bosons can lead to changes in the coherence which result in different evolution speeds and therefore different fidelities of the final states.